Analytical Solutions for a Deep-Buried Tunnel with Noncircular Cross Sections in Orthotropic Rock Mass. (20th September 2022) - Liu, Shuhong; Duan, Jiajun; Wu, Chenhao; Zhu, Yongquan
Abstract : For the generalized plane strain problem of a deep-buried tunnel excavated in orthotropic rock mass under far-field biaxial compression, the stress and displacement are the most important basis for determining tunnel support design. First, by using the complex variable method, the conformal mapping and affine transformation functions are represented by the same variable. Two stress functions are obtained by the integral method, and thus, the analytical solutions for stress and displacement in orthotropic rock mass are obtained. Second, taking a horseshoe-shaped tunnel as an example, the stress and displacement distributions around the tunnel are given by using the analytical and the finite element method software ANSYS, respectively. The analytical and numerical results are in good agreement, especially at the tunnel edge. Finally, compared with isotropic rock mass, the results show that material constants of the rock mass have little effect on the stress and significant effect on the displacement.